2015
DOI: 10.18632/oncotarget.5309
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-506 suppresses tumor proliferation and metastasis in colon cancer by directly targeting the oncogene EZH2

Abstract: Increasing evidence reveals that aberrant expression of microRNA contributes to the development and progression of colon cancer, but the roles of microRNA-506 (miR-506) in colon cancer remain elusive. Here, we demonstrated that miR-506 was down-regulated in colon cancer tissue and cells and that miR-506 expression was inversely correlated with EZH2 expression, tumor size, lymph node invasion, TNM stage and metastasis. A high level of miR-506 identified patients with a favorable prognosis. In vitro and in vivo … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
62
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(66 citation statements)
references
References 40 publications
4
62
0
Order By: Relevance
“…Furthermore, prior studies have also investigated how SFRP1 deficiency is linked with malignancies, including kidney cancer, colorectal cancer and breast cancer [25][26][27]. In our study, the SFRP1 mRNA and protein expression levels were significantly lower in bladder cancer tissues and cells compared to those in non-cancerous tissues and normal cells, which is consistent with the study of Buim [28]. During the G2/M phase of the vector transfection of SFRP1 overexpression in J82 cells, the proliferation, invasion, and migration rates decreased significantly whereas the number of cell apoptosis substantially increased.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Furthermore, prior studies have also investigated how SFRP1 deficiency is linked with malignancies, including kidney cancer, colorectal cancer and breast cancer [25][26][27]. In our study, the SFRP1 mRNA and protein expression levels were significantly lower in bladder cancer tissues and cells compared to those in non-cancerous tissues and normal cells, which is consistent with the study of Buim [28]. During the G2/M phase of the vector transfection of SFRP1 overexpression in J82 cells, the proliferation, invasion, and migration rates decreased significantly whereas the number of cell apoptosis substantially increased.…”
Section: Discussionsupporting
confidence: 91%
“…For example, miR-27a has been identified to inhibit SFRP1 expression in glioma [13,28]. However, no literature has reported the relationship between miR-1-3p and SFRP1.…”
Section: Discussionmentioning
confidence: 99%
“…Although many therapeutic modalities including surgery, resection and chemotherapy have been established, the treatment of colon cancer is still far from ideal [2, 3]. Therefore, the development of novel, less toxic therapeutic agents is imperative to reducing the high mortality and morbidity rates associated with colon cancer [46]. …”
Section: Introductionmentioning
confidence: 99%
“…miR-506 also suppressed the proliferation and invasion of gastric cancer cells by targeting Yap1 (39). Furthermore, miR-506 served a tumorsuppressive function in hepatocellular carcinoma (40), colon cancer (28), and oral squamous cell carcinoma (41) by targeting various oncogenes. In the present study, we demonstrated the critical role of miR-506 in cervical cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Bioinformatic research revealed that FOXQ1 has a putative binding site for miR-506 (Fig. 4A), a well-recognized tumor-suppressor miRNA (28,29). A dual-luciferase reporter assay was performed to verify whether or not FOXQ1 is a target gene of miR-506.…”
Section: Foxq1 Is a Potential Target Of Mir-506mentioning
confidence: 99%